THE SIGNIFICANCE OF DIGITAL TECHNOLOGIES IN THE TRAINING OF PRIMARY SCHOOL TEACHERS IN THE SUBJECTS OF THE FIELD OF «TECHNOLOGY» - Tiahur , Vasyl (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article examines the use of digital technologies and the acquisition of relevant competencies in the preparation of future primary school teachers in the field of «Technology». This should contribute to the visualization of educational material, the development of educational-methodical and didactic materials based on mastering the relevant applied software, and in the future, in the process of the professional activity of teachers, will stimulate many students to choose priority areas of activity in technical fields.